Starbucks' brand positioning and CSR to respond to coffee sector challenges - Valova, Anastasiia (2025)
This thesis examines how Starbucks leverages brand positioning and corporate social responsibility (CSR) to address current challenges in the global coffee sector, with a particular focus on the Czech Republic. Using a mixed-methods approach, it combines qualitative interviews with Starbucks managers and a quantitative survey of Czech consumers to analyze the interplay between global brand values, local adaptation, and stakeholder perceptions. The findings show that Starbucks’ emphasis on coffee quality, a consistent customer experience, and the creation of a “third place” environment help the brand stand out in a competitive market. Starbucks’ CSR initiatives—from environmental projects to community support—are firmly embedded in both global strategy and local operations. However, the research also identifies a gap between the company’s internal commitment to CSR and consumer awareness, which limits the potential of CSR as a tool for brand loyalty and differentiation. The thesis concludes with recommendations for improving CSR communication and stakeholder engagement, and discusses limitations related to sample size, demographic representation, and the single-country focus. The results contribute to a deeper understanding of how multinational brands like Starbucks can align business strategy and social responsibility to build trust and long-term value in the coffee industry.